Holistic view on Malaysian Islamic interbank money market: A critical assessment - Saiti, Buerhan (Sultan Agung Islamic University Indonesia, 2015)

(untitled)
There are many instruments being offered in the current Islamic Interbank money market (IIMM). We can divide it into two main types: deposit and placement; and tradable securities. Mudharabah Interbank Instrument (MII), Wadiah Acceptance, Commodity Murabahah (CM) and Wakalah Investment Account (WIA) are categorized as deposit and placement instruments. These instruments serve similar purposes as those of conventional bank deposit and placement instruments, though the contract, product structure and method of applications are not the same. On the other hand, tradable securities are more efficient instruments for managing liquidity. There are several such securities that are currently traded in IIMM; Government Investment Issue (GII), Bank Negara Monetary Notes-i (BNMN-i), Sell and buy Back Agreement (SBBA), Sukuk Mudharabah Cagamas (SMC), Islamic Accepted Bills (IAB), Islamic Negotiable Instruments (INI) and Islamic Securities (sukuk). In this paper, we discuss the products and services of IIMM, their modus operandi as well as Shariah issues and risks associated with IIMM. There are three main risks highlighted and discussed i.e. market risk, credit risk and operational risk.